Evidence-making interventions in health: A conceptual framing - Rhodes, Tim; Lancaster, Kari (Social science & medicine (1982), 2019)
We outline a framework for conceptualising interventions in health as ‘evidence-making interventions'. An evidence-making intervention (EMI) approach is distinct from a mainstream evidence-based intervention (EBI) approach in that it attends to health, evidence and intervention as matters of local knowledge-making practice. An EMI approach emphasises relational materiality and performativity, engaging with interventions, and their knowing, as matters-of-practice. Rather than concentrating on how ‘evidenced interventions' are implemented ‘into’ given ‘contexts' – as if evidence, intervention and context were stable and separate – an EMI approach focuses on the processes and practices through which ‘evidence’, ‘intervention’ and ‘context’ come to be. There are two strands to our analysis. First, we identify concepts to think-with in an EMI approach; and second, we illustrate their implications through case examples. We first reflect on developments in ‘implementation science’ to distinguish how an EMI approach thinks differently. We note a ‘within-limits contingency’ of implementation science in contrast to the ‘open contingency’ of an EMI approach. This helps notice the performativity of science and intervention as evidencing-making practices. We next conceptualise an EMI approach in relation to: ‘objects and practices'; ‘effects and events'; and ‘concerns and care’. We position an EMI approach in relation to theories of ‘relational materialism’, arguing that this affords a more critical, as well as more careful, way of knowing and doing health intervention. •Outlines a framework for conceptualising interventions in health as ‘evidence-making interventions'.•Offers conceptual tools for building a ‘relational material’ approach to implementation science.•Calls attention to the ‘within-limits contingency’ of current implementation science approaches.•Uses examples to illustrate the potential benefits of an evidence-making intervention approach.